Additions to the knowledge of the ground sloth Catonyx tarijensis (Xenarthra, Pilosa) in the Pleistocene of Argentina - Miño Boilini, Ángel Ramón (2015)
Quaternary Scelidotheriinae (Mammalia, Xenarthra, Mylodontidae) are represented by three genera: Scelidotherium Owen, Valgipes Gervais, and Catonyx Ameghino. The genus Catonyx includes three species of ground sloths: C. cuvieri (Lund), C. tarijensis (Gervais and Ameghino), and C. chiliensis (Lydekker). Catonyx tarijensis and C. chiliensis were present during the Quaternary of Argentina. The aim of this contribution is to improve the knowledge of C. tarijensis of Argentina from a morphological, systematic, and biostratigraphic point of view. The presence of C. tarijensis is recorded in the Ensenadan–Lujanian South American Land Mammal Ages (SALMAs) (Early Pleistocene–Late Pleistocene) of Buenos Aires Province, in the Lujanian SALMA (Late Pleistocene) of Corrientes Province, and in the Pleistocene of Córdoba and Salta Provinces. Outside Argentina, this species is recorded in the Late Pleistocene of Bolivia and Uruguay.